Strategic human resource development: A study of training and development in Nepalese commercial banks - Niraula, Ganesh Pd.; Kharel, ShreeKrishna; Shrestha, Rohit Kr. (Journal of Nepalese Management Academia, 2023)
The purpose of this study is to determine how strategic human resource development has been taken in the context of training and development by the employees of Nepalese commercial banks. Strategic human resource development has greater focus on training and development which can enable the management of banks to make appropriate policies and programs to strengthen the banks’ profitability and efficiency. The qualitative case study research design is used in this study. Three research questions were set to seek the answers from the participants/ informants of commercial banks which were related to strategic human resource development (SHRD) and its relationship with training and development, SHRD and their issues in Nepalese commercial banks and new roles and structure that improve SHRD for training and development. Some human resource officials were taken as informants/participants from different commercial banks to furnish the answers. Data were gathered in verbatim form, transcribed, coded, and generated theme using qualitative data software Atlas-ti. This study concludes that SHRD can be a challenge for Nepalese commercial banks because of inadequate investment and a lack of alignment in T&D, by evaluating needs, determining essential skills, and implementing the appropriate programs that SHRD synchronizes T&D with business objectives, it may be useful to implement new structures and roles to enhance SHRD in Nepalese commercial banks.